2021
DOI: 10.3390/cancers13102398
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Time Interval between Hepatic Resection and Liver Transplantation on Clinical Outcome in Patients with Hepatocellular Carcinoma

Abstract: Hepatic resection (HR) for hepatocellular carcinoma (HCC) may require secondary liver transplantation (SLT). However, a previous HR is supposed to worsen post-SLT outcomes. Data of patients treated by SLT between 2000 and 2018 at two tertiary referral centers were analyzed. The primary outcome of the study was to analyze the impact of HR on post-LT complications. A Comprehensive Complication Index ≥ 29.6 was chosen as cutoff. The secondary outcome was HCC-related death by means of competing-risk regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Other immunosuppressive cells, such as regulatory T cells, myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages, hepatic stellate cells, hepatocytes, and other similar cells have also been demonstrated to play a role in liver immunosuppression (31). Previous study has shown that among liver cancer patients receiving systemic chemotherapy, patients without intrahepatic lesions had higher ORR values (32). How to overcome the unfavorable immunosuppressive mechanisms in the microenvironment of the liver to improve the efficacy of immunotherapy needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Other immunosuppressive cells, such as regulatory T cells, myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages, hepatic stellate cells, hepatocytes, and other similar cells have also been demonstrated to play a role in liver immunosuppression (31). Previous study has shown that among liver cancer patients receiving systemic chemotherapy, patients without intrahepatic lesions had higher ORR values (32). How to overcome the unfavorable immunosuppressive mechanisms in the microenvironment of the liver to improve the efficacy of immunotherapy needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, improved long-term outcomes at high-volume hospitals have already been demonstrated to be a surrogate marker also for several conditions associated with HCC including better management of chronic liver disease, postresection cancer surveillance, and more aggressive treatment in case of recurrence 28,31,45. Among all the available surgical therapies to treat tumor recurrence after HR, SLT represents a valid option when offered within transplantable criteria, thus removing at the same time cancer and the underlying cirrhosis that generated it 46,47. However, due to the scarcity of organs, every attempt to rescue these patients without affecting the donor pool should be made, and repeat hepatectomy (RH) represents nowadays a more attractive alternative to SLT.…”
Section: Discussionmentioning
confidence: 99%
“…28,31,45 Among all the available surgical therapies to treat tumor recurrence after HR, SLT represents a valid option when offered within transplantable criteria, thus removing at the same time cancer and the underlying cirrhosis that generated it. 46,47 However, due to the scarcity of organs, every attempt to rescue these patients without affecting the donor pool should be made, and repeat hepatectomy (RH) represents nowadays a more attractive alternative to SLT. A recent meta-analysis comparing SLT with RH showed that SLT was inferior to RH with regard to perioperative outcomes but with better results in terms of OS and DFS.…”
Section: Discussionmentioning
confidence: 99%